Otrokova navezanost na mater in discipliniranje otroka - Cugmas, Zlatka (Psihološka obzorja (Ljubljana), 1998)
This study examined relations between attachment security, maternal discipline, and emerging internalization in 124 children attending a school entry programme, the first, the third or the fourth year at primary school. The quality of the child's attachment to the mother was determined using two estimation scales which covered the child's behaviour towards the mother in stressful situations. The study mostly supported the link between gentle, psychologically oriented discipline (opposite of power-oriented parental discipline), attachment security, and internalization, although the data are not very strong and consistent
Keywords: developmental psychology; razvojna psihologija; otroci; child; matere; navezanost; attachment theory; disciplina